Eating habits trajectories of students using university canteens. (13th November 2019) - Lorenzoni, V; Triulzi, I; Toncelli, L; Martinucci, I; De Bortoli, N; Natilli, M; Monreale, A; Pedreschi, D; Barale, R; Turchetti, G
Abstract: Background: Diets among the young often do not meet recommendations thus increasing the risk of developing chronic condition in adulthood. The present study aims at evaluate dynamics of eating habits among university students using data automatically recorded by cashier transactions at canteen. Methods: The study population consisted of 8, 338 students enrolled in bachelor courses at Pisa University in 2010-2014 and accessing canteens at least once all over their courses duration (three year). Analyses were performed merging the administrative archive of the University of Pisa and the database of cashier transactions at university canteens. The frequency of different food-groups choice over years was evaluated using a zero- and one-inflated beta regression models, while latent class analysis (LCA) and posterior probabilities derived from that were used to evaluate the evolution of eating habits. Results: In adjusted models, the proportion of fruit choices increased significantly in both the second (β = 0.077[0.013]) and third year of registration (β = 0.233[0.018]), similarly for vegetables (β = 0.090[0.011] and β = 0.065[0.015]). Conversely, the selection of foods commonly labelled as unhealthy decreased over registration years. LCA revealed 4 different classes each year. The 4 classes distinguished "healthy eaters" (LC1), those often choosing sweets, potatoes and legumes (LC2 "lazy eaters"), "greedy and quick eaters" (LC3) favoring the selection of fried foods, sandwiches and sweets while LC4 represented "selective eaters" composing their meals combining mainly grains and vegetables. The probability of being a "lazy" or "greedy and quick" eaters declined significantly overs registration years. "Selective eaters" almost doubled over years while the probability of belonging to the "healthy" class showed a weak increase over years. Conclusions: During the years following enrollment students tended to limit choices towards unhealthy foods in favors of healthier dishes. Key messages: Intervention for the promotion of healthy eating among young adults is essential as awareness of choices may raised only in adulthood. The present work outline the use of digital traces for public health research.